Cross Sectional Assessment of Knowledge of Mothers of Under Five Children Regarding Infant and Young Child Feeding and Immunization in Ujjain Block - Sajjan Gupta; Rashmi Bhujade (Medsci Publications, 2019)
Background: UNICEF has advocated use of under five mortality rate as an indicator of development .Under National Health Policy 2017 ,goal is to achieve 23 Per 1000 under five mortality by 2025.Optimal IYCF (Infant and young child feeding) and immun- ization practices are identified as interventions to reduce the under -5 mortality rate. Material and Method: Cross-sectional community based study was conducted in Ujjain block on 400 mothers, with the help of proforma. Knowledge was assessed regarding12 aspects of IYCF and 4 aspects of immunization. Results: Odds ratio was calculated and t-test was applied for anal- ysis. Overall mean IYCF knowledge score was found to be 5.12 out of 12.Overall mean immunization knowledge score was found to be 2.53 out of 4.Better knowledge, was found to be statistically sig- nificantly associated with Residence & literacy of mothers, as the mean knowledge score were significantly higher for literate and mothers from urban area. Conclusion: Knowledge of under five mothers was not found sat- isfactory. Urban and literate mothers had more knowledge regard- ing IYCF and immunization.